High-strength mining cable
By using polyvinyl chloride resin, neoprene, ethylene-vinyl acetate copolymer and core-shell SiO2@BN composite materials, existing high-strength mining cables are easily threatened by wear, corrosion and fire in complex environments, and higher wear resistance, acid and alkali resistance and fire flame retardant performance are achieved.
Patent Information
- Application Number
- CN202510196998.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-05-02
AI Technical Summary
Existing high-strength mining cables are susceptible to wear, corrosion and fire threats in complex geological conditions and chemical environments, affecting their service life and safety.
The cable is enhanced by using polyvinyl chloride resin, neoprene, ethylene-vinyl acetate copolymer and core-shell SiO2@BN composite materials through specific ratios and processes.
It significantly improves the wear resistance, acid and alkali resistance and fire resistance of the cable, and enhances its service life and safety in complex mine environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a high-strength mining cable. Background Art
[0002] In the field of mining, mining cables, as one of the key equipment, bear the important responsibilities of power transmission and signal control. Especially in the complex and changeable mining environment, mining cables not only need to have high-strength mechanical properties to withstand various external impacts, but also need to meet multiple performance requirements such as corrosion resistance, waterproofness, and fire resistance. Therefore, the development of a high-strength mining cable is of great significance to improving the safety and efficiency of mine operations.
[0003] High-strength mining cables usually refer to those cables that are made of special materials and technologies and have excellent mechanical strength, wear resistance, corrosion resistance and electrical performance. The conductor part of this type of cable is usually made of high-quality copper or aluminum to ensure good current transmission capacity; the insulation layer is made of high-strength and high-wear-resistant materials, such as polyvinyl chloride (PVC) or cross-linked polyethylene (XLPE), to resist the humid environment and mechanical damage in the mine; the sheath layer is made of high-strength and corrosion-resistant materials, such as short fiber rubber or special alloys, to protect the cable from erosion by the external environment.
[0004] Although the performance of existing high-strength mining cables has been significantly improved, there are still some problems that need to be solved. The complex geological conditions and mechanical equipment operation in the mine may cause mechanical damage such as wear, extrusion and tearing to the cable, affecting the service life and safety of the cable. There may be acid and alkali solutions or corrosive gases in the mine. These chemicals will corrode the insulation layer and sheath layer of the cable; at the same time, the humidity in the mine environment is high, and the cable is easily affected by moisture, which in turn affects its electrical and insulation properties. The temperature in the mine fluctuates greatly, which places high demands on the performance stability of the cable; in addition, the mine is a high-risk area for fire, and the cable must have good fire resistance and flame retardant properties.
[0005] In order to solve the above technical problems, the present invention proposes a new high-strength mining cable. Summary of the invention
[0006] The invention provides a high-strength mining cable, which enhances the wear resistance and acid and alkali resistance of the mining cable and has certain fireproof and flame retardant properties.
[0007] The technical solution of the present invention is as follows: In the first aspect, the present invention proposes a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 75-85 parts of polyvinyl chloride resin, 25-35 parts of chloroprene rubber, 20-30 parts of ethylene-vinyl acetate copolymer, 26-28 parts of core-shell SiO2@BN composite material, 14-16 parts of silane coupling agent modified calcium carbonate, 8-10 parts of carbon black, 4-6 parts of magnesium oxide, 10-15 parts of aluminum hydroxide, 5-7 parts of magnesium hydroxide, 0.5-1.5 parts of antioxidant, 0.8-1.2 parts of vulcanizer and 0.7-0.9 parts of co-vulcanizer.
[0008] As a further technical solution, the preparation method of the core-shell SiO2@BN composite material includes: adding the ethyl orthosilicate prehydrolyzate dropwise to the boron nitride suspension, adding ammonia water with a mass concentration of 20%-25%, adjusting the pH to 9.5±0.2, stirring the reaction in a constant temperature water bath at 60-70°C for 10-12 hours, collecting the precipitate by centrifugation, washing, pre-drying at 55-65°C for 5-6 hours, and then heating to 75-85°C for drying for 20-24 hours to obtain the core-shell SiO2@BN composite material.
[0009] As a further technical solution, the preparation method of the ethyl orthosilicate prehydrolysis solution includes: mixing ethanol and deionized water, slowly adding ethyl orthosilicate to the mixed solvent, and magnetically stirring for 10-14 minutes to form the ethyl orthosilicate prehydrolysis solution; wherein the volume ratio of ethanol, deionized water and ethyl silicate is 50-60:8-10:1.5-2.
[0010] As a further technical solution, the preparation method of the boron nitride suspension comprises: adding boron nitride powder to anhydrous ethanol, ultrasonically dispersing for 30-40 minutes, adding hexadecyltrimethylammonium bromide, and stirring for 40-60 minutes to obtain the suspension; wherein the amount ratio of the boron nitride powder, anhydrous ethanol and hexadecyltrimethylammonium bromide is 0.8-1.2g:50-60mL:0.004-0.006g.
[0011] As a further technical solution, the rate of adding the ethyl orthosilicate prehydrolyzate dropwise into the boron nitride suspension is 0.1-0.12 mL / min.
[0012] As a further technical solution, the preparation method of the silane coupling agent modified calcium carbonate comprises: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 68%-72%, adjusting the pH to 9-10, and stirring at 55-65°C for 30-40 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, stirring at room temperature for 20-30 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 25%-35%, adding the silane coupling agent solution, stirring at 400-500 rpm for reaction at a temperature of 75-85°C for 2-3 hours, filtering to remove moisture, vacuum drying at 100-110°C for 10-12 hours, and crushing to pass through a 400-mesh sieve.
[0013] As a further technical solution, the silane coupling agent is silane coupling agent WD-51.
[0014] As a further technical solution, during the preparation of the silane coupling agent solution, the weight ratio of the silane coupling agent, ethanol and water is 1:5-6:0.1-0.2.
[0015] As a further technical solution, the dosage of the silane coupling agent is 2%-3% of the mass of the calcium carbonate filter cake.
[0016] As a further technical solution, the antioxidant is antioxidant 1010; the vulcanizing agent is dicumyl peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0017] In a second aspect, the present invention provides a method for preparing a high-strength mining cable, the steps comprising: The polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at a temperature of 80-85°C for 8-10 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at a temperature of 110-115°C for 10-12 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0018] The working principle and beneficial effects of the present invention are: In the present invention, polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are used as the main base materials of the cable, providing good mechanical properties and chemical stability. Polyvinyl chloride resin has good insulation properties and acid and alkali resistance; chloroprene rubber enhances the wear resistance and weather resistance of the cable; and ethylene-vinyl acetate copolymer helps to improve the flexibility and processing performance of the cable. The reasonable proportion of these raw materials enables the cable to have good comprehensive properties while maintaining strength.
[0019] The core-shell SiO2@BN composite material of the present invention coats silicon dioxide on the surface of boron nitride (BN) to form a core-shell structure with excellent performance. SiO2, as a coating layer, has high hardness and wear resistance. Through the optimized drying process, it can be ensured that the SiO2 coating layer is completely and tightly attached to the BN core, thereby improving the overall wear resistance of the composite material. In addition, when the SiO2@BN composite material is used as a filler for mining cables, it can effectively prevent the spread of flames and the transfer of heat. In addition, the SiO2 coating layer can further improve the thermal insulation performance of the composite material, so that it can better protect the inside of the cable from damage in a fire. Therefore, the addition of this composite material not only improves the wear resistance and acid and alkali resistance of the cable, but also improves the performance of the cable in high temperature or harsh environments through its unique thermal stability and lubricity.
[0020] In the process of preparing the core-shell SiO2@BN composite material of the present invention, the hydroxyl (-OH) active sites on the surface of boron nitride are enhanced by electrostatic adsorption of CTAB and weak etching of ammonia water; then a two-step temperature rising drying method is used, and the temperature is slowly raised during the drying process to ensure that the moisture and other volatile substances in the composite material are gradually and evenly released. This step helps to further consolidate the bonding force between the SiO2 coating layer and the BN core and prevent the coating layer from cracking.
[0021] In the present invention, a silane coupling agent is used to improve the compatibility between calcium carbonate and a polymer substrate, thereby improving the mechanical properties and heat resistance of the cable. The calcium carbonate modified by the silane coupling agent can be more evenly dispersed in the polymer substrate, reducing the possibility of stress concentration and crack generation, thereby improving the wear resistance and durability of the cable. In addition, when the calcium carbonate modified by the silane coupling agent can also produce a synergistic effect with the core-shell SiO2@BN composite material, when the calcium carbonate modified by the silane coupling agent is mixed with other inorganic materials such as the SiO2@BN composite material, since the silane coupling agent on the surface of the calcium carbonate particles has formed a good compatibility with the polymer matrix, this helps to drive the dispersion of other inorganic material particles in the polymer matrix; after the calcium carbonate is modified by the silane coupling agent, the organic functional groups on its surface can also interact with the functional groups on the surfaces of other inorganic material particles, further enhancing the dispersibility and compatibility between the inorganic material particles, which is better than directly adding the silane coupling agent.
[0022] The magnesium oxide, aluminum hydroxide and magnesium hydroxide inorganic fillers in the present invention have good flame retardant and smoke suppression properties. When a fire occurs in the cable, they can absorb and release a large amount of heat, reduce the burning speed of the cable, and reduce the generation of toxic smoke. At the same time, these fillers can also improve the mechanical strength and heat resistance of the cable. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be noted that, in the present invention, the model of the polyvinyl chloride resin is SG-0; the model of the chloroprene rubber is CR244; the model of the ethylene-vinyl acetate copolymer is EVA 2803; and the silane coupling agent is silane coupling agent WD-51.
[0025] Example 1 The present embodiment provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, the sheath layer being composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of core-shell SiO2@BN composite material, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 parts of co-vulcanizing agent.
[0026] The preparation method of the core-shell SiO2@BN composite material includes: Add 1 g of boron nitride powder to 55 mL of anhydrous ethanol, disperse by ultrasonic for 35 minutes, add 0.005 g of hexadecyltrimethylammonium bromide, and stir for 50 minutes to obtain a boron nitride suspension. Mix 55 mL of ethanol and 9 mL of deionized water, slowly drop 1.7 mL of tetraethyl orthosilicate into the mixed solvent, and stir magnetically at 250 r / min for 12 min to form a tetraethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.11 mL / min. Ammonia water with a mass concentration of 22% was added, and the pH was adjusted to 9.5±0.2. The magnetic stirring rate was controlled to be 550 r / min, and the reaction was carried out in a constant temperature water bath at 65°C for 11 hours. The reaction solution was centrifuged at 8500 r / min for 7 minutes, and the precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The product was pre-dried at 60°C for 5.5 hours, and then heated to 80°C for drying for 22 hours to obtain a core-shell SiO2@BN composite material.
[0027] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0028] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0029] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0030] Example 2 The present embodiment provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, the sheath layer being composed of the following raw materials in parts by weight: 75 parts of polyvinyl chloride resin, 25 parts of chloroprene rubber, 20 parts of ethylene-vinyl acetate copolymer, 26 parts of core-shell SiO2@BN composite material, 14 parts of silane coupling agent modified calcium carbonate, 8 parts of carbon black, 4 parts of magnesium oxide, 10 parts of aluminum hydroxide, 5 parts of magnesium hydroxide, 0.5 parts of antioxidant, 0.8 parts of vulcanizing agent and 0.7 parts of co-vulcanizing agent.
[0031] The preparation method of the core-shell SiO2@BN composite material includes: Add 0.8 g of boron nitride powder to 50 mL of anhydrous ethanol, disperse by ultrasonic for 30 minutes, add 0.004 g of hexadecyltrimethylammonium bromide, stir for 40 minutes, and obtain the obtained product. Mix 50 mL of ethanol and 8 mL of deionized water, slowly drop 1.5 mL of tetraethyl orthosilicate into the mixed solvent, and stir magnetically at 200 r / min for 10 min to form a tetraethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.1 mL / min. Ammonia water with a mass concentration of 20% was added to adjust the pH to 9.5±0.2. The magnetic stirring rate was controlled to be 500 r / min. The mixture was reacted in a constant temperature water bath at 60°C for 10 hours. The reaction solution was centrifuged at 8000 r / min for 5 minutes. The precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The mixture was pre-dried at 55°C for 5 hours and then heated to 75°C for 20 hours to obtain a core-shell SiO2@BN composite material.
[0032] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 68%, adjusting the pH to 9, and stirring at 55°C for 30 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5:0.1, stirring at room temperature for 20 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 25%, adding a silane coupling agent solution, wherein the amount of the silane coupling agent is 2% of the mass of the calcium carbonate filter cake, stirring at 400 rpm for 2 hours at a temperature of 75°C, filtering to remove moisture, vacuum drying at 100°C for 10 hours, and crushing to pass through a 400-mesh sieve.
[0033] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0034] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 80°C for 8 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 110°C for 10 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0035] Example 3 The present embodiment provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, the sheath layer being composed of the following raw materials in parts by weight: 85 parts of polyvinyl chloride resin, 35 parts of chloroprene rubber, 30 parts of ethylene-vinyl acetate copolymer, 28 parts of core-shell SiO2@BN composite material, 16 parts of silane coupling agent modified calcium carbonate, 10 parts of carbon black, 6 parts of magnesium oxide, 15 parts of aluminum hydroxide, 7 parts of magnesium hydroxide, 1.5 parts of antioxidant, 1.2 parts of vulcanizing agent and 0.9 parts of co-vulcanizing agent.
[0036] The preparation method of the core-shell SiO2@BN composite material includes: Add 1.2 g of boron nitride powder to 60 mL of anhydrous ethanol, disperse by ultrasonic for 40 minutes, add 0.006 g of hexadecyltrimethylammonium bromide, stir for 60 minutes, and obtain the product after stirring for 50 minutes. Mix 60 mL of ethanol and 10 mL of deionized water, slowly drop 2 mL of ethyl orthosilicate into the mixed solvent, and stir magnetically at 300 r / min for 14 min to form a ethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.12 mL / min. Ammonia water with a mass concentration of 25% was added, and the pH was adjusted to 9.5±0.2. The magnetic stirring rate was controlled to be 600 r / min, and the reaction was carried out in a constant temperature water bath at 70°C for 12 hours. The reaction solution was centrifuged at 9000 r / min for 10 min, and the precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The precipitate was pre-dried at 65°C for 6 hours, and then heated to 85°C for drying for 24 hours to obtain a core-shell SiO2@BN composite material.
[0037] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 72%, adjusting the pH to 10, and stirring at 65°C for 40 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:6:0.2, stirring at room temperature for 30 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 35%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 3% of the mass of the calcium carbonate filter cake, stirring at 500 rpm for 3 hours at a temperature of 85°C, filtering to remove water, vacuum drying at 110°C for 12 hours, and crushing to pass through a 400-mesh sieve.
[0038] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0039] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 85°C for 10 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 115°C for 12 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0040] Comparative Example 1 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of core-shell SiO2@BN composite material, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0041] The preparation method of the core-shell SiO2@BN composite material includes: Add 1 g of boron nitride powder to 55 mL of anhydrous ethanol, disperse by ultrasonic for 35 minutes, add 0.005 g of hexadecyltrimethylammonium bromide, and stir for 50 minutes to obtain a boron nitride suspension. Mix 55 mL of ethanol and 9 mL of deionized water, slowly drop 1.7 mL of tetraethyl orthosilicate into the mixed solvent, and stir magnetically at 250 r / min for 12 min to form a tetraethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.11 mL / min. Ammonia water with a mass concentration of 22% was added, and the pH was adjusted to 9.5±0.2. The magnetic stirring rate was controlled to be 550 r / min, and the reaction was carried out in a constant temperature water bath at 65°C for 11 hours. The reaction solution was centrifuged at 8500 r / min for 7 minutes, and the precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The precipitate was dried at 80°C for 27.5 hours to obtain a core-shell SiO2@BN composite material.
[0042] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0043] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0044] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0045] Comparative Example 2 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of core-shell SiO2@BN composite material, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0046] The preparation method of the core-shell SiO2@BN composite material includes: Add 1g of boron nitride powder into 55mL of anhydrous ethanol and disperse it ultrasonically for 35 minutes to obtain a boron nitride suspension. Mix 55 mL of ethanol and 9 mL of deionized water, slowly drop 1.7 mL of tetraethyl orthosilicate into the mixed solvent, and stir magnetically at 250 r / min for 12 min to form a tetraethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.11 mL / min. Ammonia water with a mass concentration of 22% was added, and the pH was adjusted to 9.5±0.2. The magnetic stirring rate was controlled to be 550 r / min, and the reaction was carried out in a constant temperature water bath at 65°C for 11 hours. The reaction solution was centrifuged at 8500 r / min for 7 minutes, and the precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The product was pre-dried at 60°C for 5.5 hours, and then heated to 80°C for drying for 22 hours to obtain a core-shell SiO2@BN composite material.
[0047] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0048] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0049] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0050] Comparative Example 3 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of nano-silicon dioxide, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0051] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0052] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0053] The preparation method of the high-strength mining cable comprises the following steps: The polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then nano-silica, silane coupling agent-modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0054] Comparative Example 4 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of boron nitride powder, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0055] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0056] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0057] The preparation method of the high-strength mining cable comprises the following steps: The polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then boron nitride powder, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0058] Comparative Example 5 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 15 parts of silane coupling agent modified calcium carbonate, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0059] The preparation method of silane coupling agent modified calcium carbonate includes: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 70%, adjusting the pH to 9.5, and stirring at 60°C for 35 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, wherein the weight ratio of the silane coupling agent, ethanol and water is 1:5.5:0.15, stirring at room temperature for 25 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 30%, adding the silane coupling agent solution, wherein the amount of the silane coupling agent is 2.5% of the mass of the calcium carbonate filter cake, stirring at 450 rpm for 2.5 hours at a temperature of 80°C, removing moisture by filtering, vacuum drying at 105°C for 11 hours, and crushing to pass through a 400-mesh sieve.
[0060] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0061] The preparation method of the high-strength mining cable comprises the following steps: The polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then silane coupling agent-modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0062] Comparative Example 6 The comparative example provides a high-strength mining cable, comprising a core and a sheath layer coated on the surface of the core, wherein the sheath layer is composed of the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 30 parts of chloroprene rubber, 25 parts of ethylene-vinyl acetate copolymer, 27 parts of core-shell SiO2@BN composite material, 15 parts of silane coupling agent, 9 parts of carbon black, 5 parts of magnesium oxide, 12 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 1 part of antioxidant, 1 part of vulcanizing agent and 0.8 part of co-vulcanizing agent.
[0063] The preparation method of the core-shell SiO2@BN composite material includes: Add 1 g of boron nitride powder to 55 mL of anhydrous ethanol, disperse by ultrasonic for 35 minutes, add 0.005 g of hexadecyltrimethylammonium bromide, and stir for 50 minutes to obtain a boron nitride suspension. Mix 55 mL of ethanol and 9 mL of deionized water, slowly drop 1.7 mL of tetraethyl orthosilicate into the mixed solvent, and stir magnetically at 250 r / min for 12 min to form a tetraethyl orthosilicate prehydrolyzate; Boron nitride suspension was added dropwise to the tetraethyl orthosilicate prehydrolyzate, and the dropping speed was controlled to be 0.11 mL / min. Ammonia water with a mass concentration of 22% was added, and the pH was adjusted to 9.5±0.2. The magnetic stirring rate was controlled to be 550 r / min, and the reaction was carried out in a constant temperature water bath at 65°C for 11 hours. The reaction solution was centrifuged at 8500 r / min for 7 minutes, and the precipitate was collected and washed with ethanol and deionized water for 3 times in sequence to remove unreacted tetraethyl orthosilicate and hexadecyltrimethylammonium bromide. The product was pre-dried at 60°C for 5.5 hours, and then heated to 80°C for drying for 22 hours to obtain a core-shell SiO2@BN composite material.
[0064] The antioxidant is antioxidant 1010; the vulcanizing agent is diisopropylbenzene peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
[0065] The preparation method of the high-strength mining cable comprises the following steps: Polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at 82°C for 9 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed, and then kneaded at 112°C for 11 minutes; after kneading and granulation in an extruder, it is extruded and coated on the surface of the bundled wire core, and after cooling, a high-strength mining cable is formed.
[0066] Test Example 1: The high-strength mining cables prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-6 were tested as follows: 1. Tensile strength: Tested in accordance with GB / T2951.11-2008; 2. Wear resistance: Referring to EN 651-2011 standard, the wear test was carried out using the FRICK-TABER falling sand abrasion method, with a load of 9.8±0.1N and a falling sand speed of 21±3g / min; 3. Acid resistance: The test temperature is 25°C. Soak the sample in a 10% hydrochloric acid solution for one month to observe whether the surface is bubbling or damaged. 4. Alkali resistance: The test temperature is 25°C. Soak the sample in a 10% sodium hydroxide solution for one month to observe whether the surface is bubbling or damaged. 5. Oxygen index: Tested in accordance with GB / T 2406.2-2009.
[0067] The test results are shown in Table 1 below: Table 1
[0068] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength mining cable, characterized in that: The invention comprises a wire core and a sheath layer coated on the surface of the wire core, wherein the sheath layer is composed of the following raw materials in parts by weight: 75-85 parts of polyvinyl chloride resin, 25-35 parts of chloroprene rubber, 20-30 parts of ethylene-vinyl acetate copolymer, 26-28 parts of core-shell SiO2@BN composite material, 14-16 parts of silane coupling agent modified calcium carbonate, 8-10 parts of carbon black, 4-6 parts of magnesium oxide, 10-15 parts of aluminum hydroxide, 5-7 parts of magnesium hydroxide, 0.5-1.5 parts of antioxidant, 0.8-1.2 parts of vulcanizer and 0.7-0.9 parts of co-vulcanizer.
2. A high-strength mining cable according to claim 1, characterized in that: The preparation method of the core-shell SiO2@BN composite material comprises: adding a pre-hydrolyzed ethyl orthosilicate solution dropwise into a boron nitride suspension, adding ammonia water with a mass concentration of 20%-25%, adjusting the pH to 9.5±0.2, stirring and reacting in a constant temperature water bath at 60-70°C for 10-12 hours, collecting the precipitate by centrifugation, washing, pre-drying at 55-65°C for 5-6 hours, and then heating to 75-85°C for drying for 20-24 hours to obtain the core-shell SiO2@BN composite material.
3. A high-strength mining cable according to claim 2, characterized in that: The preparation method of the ethyl orthosilicate prehydrolysis solution comprises: mixing ethanol and deionized water, slowly dropping ethyl orthosilicate into the mixed solvent, and magnetically stirring for 10-14 minutes to form the ethyl orthosilicate prehydrolysis solution; wherein the volume ratio of ethanol, deionized water and ethyl silicate is 50-60:8-10:1.5-2.
4. A high-strength mining cable according to claim 2, characterized in that: The preparation method of the boron nitride suspension comprises: adding boron nitride powder into anhydrous ethanol, ultrasonically dispersing for 30-40 minutes, adding hexadecyltrimethylammonium bromide, and stirring for 40-60 minutes to obtain the suspension; wherein the amount ratio of the boron nitride powder, anhydrous ethanol and hexadecyltrimethylammonium bromide is 0.8-1.2g:50-60mL:0.004-0.006g.
5. A high-strength mining cable according to claim 2, characterized in that: The speed of adding the ethyl orthosilicate prehydrolyzate dropwise into the boron nitride suspension is 0.1-0.12 mL / min.
6. A high-strength mining cable according to claim 1, characterized in that: The preparation method of the silane coupling agent modified calcium carbonate comprises: dispersing nano calcium carbonate in water to obtain a slurry with a solid content of 68%-72%, adjusting the pH to 9-10, and stirring at 55-65° C. for 30-40 minutes; filtering to obtain a calcium carbonate filter cake for standby use; dissolving a silane coupling agent in a mixed solution of ethanol and water, stirring at room temperature for 20-30 minutes to obtain a silane coupling agent solution, dispersing the calcium carbonate filter cake in deionized water, controlling the solid content to 25%-35%, adding the silane coupling agent solution, stirring at 400-500 rpm for reaction at a temperature of 75-85° C. for 2-3 hours, filtering to remove water, vacuum drying at 100-110° C. for 10-12 hours, and crushing to pass through a 400-mesh sieve to obtain the obtained product.
7. A high-strength mining cable according to claim 6, characterized in that: During the preparation of the silane coupling agent solution, the weight ratio of the silane coupling agent, ethanol and water is 1:5-6:0.1-0.
2.
8. A high-strength mining cable according to claim 6, characterized in that: The dosage of the silane coupling agent is 2%-3% of the mass of the calcium carbonate filter cake.
9. A high-strength mining cable according to claim 1, characterized in that: The antioxidant is antioxidant 1010; the vulcanizing agent is dicumyl peroxide; and the co-vulcanizing agent is triallyl isocyanurate.
10. The method for preparing a high-strength mining cable according to any one of claims 1 to 9, characterized in that the steps include: The polyvinyl chloride resin, chloroprene rubber and ethylene-vinyl acetate copolymer are mixed and kneaded at a temperature of 80-85°C for 8-10 minutes, and then core-shell SiO2@BN composite material, silane coupling agent modified calcium carbonate, carbon black, magnesium oxide, aluminum hydroxide, magnesium hydroxide, antioxidant, vulcanizer and co-vulcanizing agent are added and mixed. After kneading at a temperature of 110-115°C for 10-12 minutes, the mixture is extruded and coated on the surface of the bundled wire core, and then cooled to form a high-strength mining cable.
Citation Information
Cited By
Wear-resistant and high-temperature-resistant vehicle coating and preparation method thereof
CN120842943A
Special soldering flux for electronic product welding and preparation method thereof
CN121042766A